A new phytophagous Bracon Fabricius (Hymenoptera, Braconidae) associated with Protium ovatum Engl. (Burseraceae) fruits from Brazilian savannah - Perioto, Nelson Wanderley [UNESP]; Rosa Lara, Rogeria Ines; Ferreira, Cleidson Soares [UNESP]; Rodrigues Fernandes, Daniell Rodrigo [UNESP]; Pedroso, Elizabeth do Carmo [UNESP]; Linhares Volpe, Haroldo Xavier [UNESP]; Nais, Juliana [UNESP]; Batista Correa, Lilian Roberta [UNESP]; Viel, Silvio Rogerio [UNESP] (Magnolia Press, 2011)
Bracon zuleideae Perioto & Lara sp. nov. (Hymenoptera, Braconidae), a new species of phytophagous braconid associated with fruits of Protium ovatum Engl. (Burseraceae) is described and illustrated.
Keywords: Braconinae; Brazil; Neotropical; phytophagy; seed predation; Taxonomy